Hubungan Dukungan Sosial dengan Tingkat Kecemasan Narapidana di Lembaga Pemasyarakatan Klas II A Muaro Padang Tahun 2014 - Dewi Eka Putri; Ira Erwina; Hilma Adha (NERS Jurnal Keperawatan, 2014)
The Relationships between Social Support With level Anxiety of Inmates in Muaro Padang Instituted Society Class II A in 2014.Status as inmate is severe stressor in life, inmates lose freedom, unsecurity, uncomforted, far away from the family and society, changes in social support received and demanded to adapt to the limited environment, who the inmate have impact was been mental health problems is anxiety . The research aims to knowhow the strength of the relationship of social support with anxiety inmates level inmates in Muara Padang instituted society Class II A in2014. Research of study used is descriptive correlational with approach cross-sectional. This research was conducted on 237 respondents. The data collected using questionnaire consist of demographic data, the level of anxiety, and social support. The results is 48.5% of inmates has mild anxiety, and 52.3% inmates getting high social support. Based on the results of spearman correlation test, it is known have a significant relationship between social support and level of anxiety at Muara Padang instituted society class II A in 2014,with p =0.000 and r = -0.721,, it’s means there is a strong correlation with negative direction, the meaning higher of social support then that more be lower the level of anxiety or otherwise. Recommended for prison; office, nurses, families, and fellow inmatesto became a source of social support for prisoners so to be reduce anxiety.